Supramolecular chemistry: from aromatic foldamers to solution-phase supramolecular organic frameworks - Li, Zhan-Ting (Beilstein Journal of Organic Chemistry, 2015)
This mini-review covers the growth, education, career, and research activities of the author. In particular, the developments of various folded, helical and extended secondary structures from aromatic backbones driven by different noncovalent forces (including hydrogen bonding, donor–acceptor, solvophobicity, and dimerization of conjugated radical cations) and solution-phase supramolecular organic frameworks driven by hydrophobically initiated aromatic stacking in the cavity of cucurbit[8]uril (CB[8]) are highlighted.
Keywords: donor–acceptor interaction; foldamer; hydrogen bond; radical cation dimerization; supramolecular organic framework